The involvement factor with physical and fitness activities - Nur Asma Nazihah Adull Hamid; Nur Athirah Abdullah; Siti Nur Hadaina Rajab; Nurul Atikah Mohd Razali (2023)
Physical activity is a person's movements, including when doing leisure activities,travelling from one location to another, and working. The involvement in physical andfitness activities became important among the community in Malaysia. The primary focus of this problem statement is on health issues. People who struggle with health problemssuch as obesity typically participate in less physical and fitness activity. This research about community involvement towards physical and fitness activities. The research was conducted among communities that are basically doing physical and fitness activities.Therefore, this study aimed to examine the relationship between reduce stress, lose weight, sleep and involvement factors with physical and fitness activities. When it comes to finding information, communities in Malaysia from 18 to 26 years old and above appear for identifying involvement factors in physical and fitness activities among communities in Malaysia. 200 respondents participated in this study which was conducted through social media like Google Form, WhatsApp, Facebook, and Instagram. The result showed that reduce stress, lose weight, and sleep influence the involvement in physical and fitness activities.